Vitamin D Status Is Negatively Related to Insulin Resistance and Bone Turnover in Chinese Non-Osteoporosis Patients With Type 2 Diabetes: A Retrospective Cross-Section Research - Zhang, Jie; Li, Yangjun; Lai, Dong; Lu, Di; Lan, Zhenhao; Kang, Junfei; Xu, Yidong; Cai, Shaofang (Frontiers in Public Health, 2022)
Background and Objectives: Vitamin D status is closely related to blood glucose and bone metabolism in patients with type 2 diabetes (T2DM). Vitamin D affected bone density and bone metabolism and resulted in osteopenia and osteoporosis. Insulin resistance raised the risk of osteoporosis in T2DM patients. Our former research showed a negative relationship between insulin resistance and 25-hydroxyvitamin D concentration. The aim of the present study was to determine the association between vitamin D status and insulin resistance and bone metabolism in patients with T2DM. Subjects and Methods: A retrospective cross-section research was carried out among 109 non-osteoporosis T2DM patients. Fasting blood glucose (FBG), 25-hydroxy vitamin D [25(OH)D], fasting blood insulin (FINS), glycosylated hemoglobin (HbA1c), serum creatinine (SCr), calcium (Ca), phosphorus (P), insulin-like growth factor-1 (IGF-1) and bone alkaline phosphatase (BALP), body mass index (BMI), glomerular filtration rate (eGFR), HOMA-IR and calcium-phosphorus product were determined. Results: The average serum Calcium 2.33±0.13mmol/L, average serum P is 1.36±0.15mmol/L, BALP 184.72±14.77 u/L. Both in men and women, 25(OH)D was negatively correlated with IGF-1 (β=0. 581, p ≤ 0.001）and HOMA-IR (β= -0.349，p ≤ 0.001), and positively associated with BALP (β= -0. 182, p ≤ 0.05）after adjusting for age, BMI and eGFR. ( There was a negative relationship between HOMA-IR and IGF-1（β = -0.376, p ≤ 0.001）, and a positive relationship between HOMA-IR and BALP（β = 0.232, p ≤ 0.05）, adjusted by age, eGFR, BMI. Conclusion: Insulin resistance increased when 25(OH)D concentrations decreased, which may enhance bone turnover in patients with T2DM without osteoporosis. 25(OH)D concentrations are negatively related to both insulin resistance and bone turnover which increases the risk of osteoporosis. It is the first study that explored the relationship between serum vitamin D status, insulin resistance, and bone metabolism in Chinese non-osteoporosis patients with T2DM.